Somatostatin analogue continuation upon progression in patients with gastroenteropancreatic neuroendocrine tumour (SAUNA trial): a randomised controlled trial protocol - Suzanne Polinder; Ivan Borbath; Marc Peeters; Philippe Beutels; Elke Smits; Iris Verhaegen; Ella Roelant; Wouter Dercksen; Stella Heemskerk; Siddharth Chhajlani; Jelka Kuiper; Christophe M Deroose; et al. (BMJ Open)
Introduction Gastroenteropancreatic neuroendocrine tumours (GEP NET) are malignant neoplasms that impact survival. Somatostatin analogues (SSA) are used for treating hormonal symptoms caused by GEP NET and have antiproliferative effects. They are used as first-line therapy in patients with advanced GEP NET, but disease control is limited to a median progression-free survival (mPFS) of 14–32 months. Second-line treatment options include targeted therapy (everolimus or sunitinib), or peptide receptor radionuclide therapy (PRRT) with 177Lu-DOTATATE. In patients suffering from a NET-related hormonal syndrome, SSA is generally continued life-long. However, there is no consensus on whether it is beneficial to continue SSA in non-functional NET upon disease progression. Due to the ongoing activity of the somatostatin receptor pathway in GEP NET progressing on first-line SSA, we hypothesise that SSA have an added efficacy in second-line therapy.Methods and analysis The SAUNA trial is an international, multicentre, open-label, randomised, controlled, pragmatic clinical trial. 270 patients with advanced, non-functional GEP NET and progression under first-line SSA will be included in substudy 1 (PRRT; n=142) or substudy 2 (targeted therapy (everolimus/sunitinib); n=128) per investigator’s choice of second-line therapy and will be randomised (1:1) per substudy between SSA continuation or SSA withdrawal arms. Co-primary endpoints are the difference in progression-free survival (PFS) according to the RECIST (Response Evaluation Criteria In Solid Tumours) V.1.1 criteria and difference in time to deterioration (TTD) in quality of life (QoL) per substudy after initiating second-line therapy with or without SSA. Secondary endpoints include the PFS rate at 18 months, the difference in pooled PFS and TTD combining both substudies, overall survival, response rates, QoL, costs, cost-effectiveness and toxicity. The study design was developed in cooperation with the Belgium and Dutch patient organisations.Ethics and dissemination The study has been approved on 31 May 2023 by the Ethical Committees and Regulatory Authorities of the concerned member states (EU CT number 2022-502703-30-00). Both the trial management group and the steering committee will oversee good governance of this trial. Results of the study will be published in peer-reviewed international journals and presented at international conferences.Trial registration number NCT05701241.